The Future of US Economic Growth - Fernald, John G.; Jones, Charles I. (American Economic Review, 2014)
Modern growth theory suggests that more than three-quarters of growth since 1950 reflects rising educational attainment and research intensity. As these transition dynamics fade, US economic growth is likely to slow at some point. However, the rise of China, India, and other emerging economies may allow another few decades of rapid growth in world researchers. Finally, and more speculatively, the shape of the idea production function introduces a fundamental uncertainty into the future of growth. For example, the possibility that artificial intelligence will allow machines to replace workers to some extent could lead to higher growth in the future.